An ethnography of a Vodu shrine in southern Togo : of spirit, slave, and sea - Montgomery, Eric James. (Studies of Religion in Africa, 2017)
In this book, Eric Montgomery and Christian Vannier provide an ethnographically informed text on the cultural meanings and practices surrounding the gods and metaphysics of Vodu, as they relate to daily life in an ethnic Ewe fishing community on the coast of southern Togo. The authors approach this spirit possession and medicinal order through "shrine ethnography," understanding shrines as parts of sacred landscapes that are ecological, economic, political, and social. Giving voice to practitioners and situating shrines and Vodu itself into the history and political economy of the region make this text pertinent to the social changes and global relevance of Millennial Africa.